2016
DOI: 10.1080/10641963.2016.1182177
|View full text |Cite
|
Sign up to set email alerts
|

Ankle-brachial index and brachial-ankle pulse wave velocity are associated with albuminuria in community-based Han Chinese

Abstract: ABI and baPWV were associated with albuminuria after adjusting for other risk factors in Chinese community-based elderly Han population. The association of ABI with albuminuria was stronger in hypertension and diabetes patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
5
2
Order By: Relevance
“…It is more readily applicable in the clinic than cfPWV, since it is automated and easier to measure. The mean baPWV in our study was 1536.59 ± 305.89 cm/s, which is lower than those in Xu's study, which reported an average baPWV of 2154.50 ± 502.97 cm/s in the populations with an ABI < 0.9 and 2049.49 ± 456.65 cm/s in populations with ABI ≥ 0.9 [22]. The difference between baPWV values may be partly due to the old age of the study participants in the study by Xu (76.17 ± 6.05 years in the ABI < 0.9 group and 71.41 ± 6.48 years in the ABI ≥ 0.9 group), because age is one of the major determinants of PWV.…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…It is more readily applicable in the clinic than cfPWV, since it is automated and easier to measure. The mean baPWV in our study was 1536.59 ± 305.89 cm/s, which is lower than those in Xu's study, which reported an average baPWV of 2154.50 ± 502.97 cm/s in the populations with an ABI < 0.9 and 2049.49 ± 456.65 cm/s in populations with ABI ≥ 0.9 [22]. The difference between baPWV values may be partly due to the old age of the study participants in the study by Xu (76.17 ± 6.05 years in the ABI < 0.9 group and 71.41 ± 6.48 years in the ABI ≥ 0.9 group), because age is one of the major determinants of PWV.…”
Section: Discussioncontrasting
confidence: 94%
“…In a study conducted in Korean rural communities with participants aged over 40 years, the median baPWV was 1515 cm/s (interquartile range 1325-1764 cm/s), which is similar to that in the present study [23]. Our findings were consistent with those of another community-based cross-sectional study of 2127 community residents of Han ethnicity in Beijing, China aged 60-95 years [22]. The participants were divided into quartiles according to baPWV value: < 1730, , and > 2305 cm/s.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results are consistent with most, but not all, studies that have demonstrated robust associations of ACR with indicators of subclinical atherosclerosis. [13][14][15][16] The inconsistencies might be due to the younger age of our population and lower proportion of underlying metabolic diseases. We found significant positive associations of albuminuria (ACR≥30 mg/g) with elevated Ba-PWV and abnormal ABI, whereas a borderline significant relationship was detected for carotid atherosclerosis.…”
Section: Discussionmentioning
confidence: 95%
“…Sampling and research methods have been reported elsewhere ( 22 , 23 ). The previous study used a two-stage hierarchical cluster sampling method to conduct a population-based cross-sectional survey of participants in Wanshou Road Community, a representative urban residential area in Beijing.…”
Section: Methodsmentioning
confidence: 99%